Exploring the authentic needs of prospective ESP teachers in contributing to ESP teacher education: Indonesian ESP teachers’ perspectives - Murtafi'ah, Banatul (Journal on English as a Foreign Language, 2025)
English for specific purposes (ESP) teacher training for pre-service English teachers is needed due to the growing need for English in many professions. Though ESP teacher training is needed, this area is underexplored. This study attempts to investigate the actual needs of prospective ESP teachers. This is a qualitative case study involving six participants from three groups of Indonesian ESP teachers: two pre-service teachers, three in-service teachers, and one teacher educator. The data were collected from interviews with those participants and analyzed using thematic analysis. The finding of this study implies the need to integrate theories and practices in ESP teacher training by involving practitioners and providing opportunities to do teaching practice. Then, to become a professional ESP teacher, prospective ESP teachers should have pedagogical skills, good English proficiency, willingness to learn, and adaptability. This study implies that ESP teacher education should equip pre-service teachers with both skills and good attitudes. The tertiary education ESP program should ideally equip pre-service teachers with the basic concept of teaching ESP, one field of ESP, and a practical guide for prospective ESP teachers.